DEMS studies of the ethanol electro-oxidation on TiOC supported Pt catalysts–Support effects for higher CO2 efficiency. (1st May 2019) - Shakibi Nia, Niusha; Martucci, Alessandro; Granozzi, Gaetano; García, Gonzalo; Pastor, Elena; Penner, Simon; Bernardi, Johannes; Alonso-Vante, Nicolas; Kunze-Liebhäuser, Julia
Abstract: Direct ethanol fuel cells are highly promising energy conversion devices, but the complete oxidation of ethanol to CO2 at low temperatures is still one of the main challenges. Titanium oxycarbide (TiO1-x Cx ) powder is investigated as stable and synergistic support for Pt nanoparticles during the ethanol oxidation reaction (EOR) in acidic electrolytes. EOR products are quantitatively detected online with differential electrochemical mass spectrometry. At room temperature, Pt/TiO1-x Cx has a CO2 efficiency maximum of 8.9%, while only 1.7% are measured for Pt nanoparticles on Vulcan carbon (Pt/C). The reaction pathway is channeled towards the formation of C1 products, while C2 product formation is suppressed. This effect is expected to be much enhanced at elevated temperatures which makes TiO1-x Cx a highly interesting catalyst support material in general. Graphical abstract: Image 1 Highlights: The electrocatalytic activity of Pt/TiOC towards the EOR exceeds that of Pt/C. EOR products are quantitatively detected online with DEMS. The RT CO2 efficiency of Pt/TiOC is enhanced and outperforms that of Pt/C. The C2-pathway is largely suppressed with enhancement of the CO2 efficiency. TiO2 formation enhances the CO tolerance of Pt through a bifunctional mechanism.